POLLEN MORPHOLOGY OF THE GENUS CUSCUTA L. (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
With the help of light and scanning electron microscopes the palynomorphological investigation of 39 species of the genus Cuscuta L. has been carried out. The data obtained specify the considerable affinity of the subgenera Grammica and Cuscuta on the morphological type of pollen. At the same time, according to the palynomorphological data, the species of subgenus Monogyna occupy some isolated position in the genus Cuscuta.
Keywords: palynomorphological investigation; Cuscuta; morphological type of pollen